Pengembangan Lembar Kerja Mahasiswa Berbasis Science, Environment, Technology, and Society di Program Studi Pendidikan Kimia Universitas Muhammadiyah Pontianak - Desi Marianti; Tuti Kurniati*; Dedeh Kurniasih (Universitas Syiah Kuala, 2022)
In learning management and laboratory techniques, only explaining using power point media and giving assignments so that students do not understand the material presented. Therefore, it is necessary to have teaching materials such as student worksheets based on science, environment, technology, society (SETS). This study aims to produce valid, practical and effective media. Validity was measured from the material aspect and the media aspect using a validation sheet, practicality was measured using a student response questionnaire. While the effectiveness is measured from the value after using the LKS or posttest scores. This type of research is research and development with a thiagarajan device model, namely a 4D model that has been modified into 3D. The results of the analysis show that SETS-based worksheets with validity values of 85% and 88.75% are categorized as very valid. The results of the practicality test in the limited trial of 86.4% and the main trial of 88.02% were categorized as very practical. The results of the effectiveness test with the posttest recapitulation value in the limited trial of 78.3% and the main trial of 82.5%. Thus, SETS-based worksheets are suitable for use in the teaching and learning process on management materials and laboratory techniques